New tools for improving culture strategies for Hepatocyte differentiation - Silva, Marta Sofia Marques, 1988- (2011)
Tese de mestrado. Biologia (Biologia Molecular e Genética). Universidade de Lisboa, Faculdade de Ciências, 2011